Dinoflagellate Cyst Distribution in Relation to the Sediment Composition and Grain Size in the Coastal Area of Pangkajene, South Sulawesi, Indonesia - Arief Rachman; Hikmah Thoha; Mariana Destila Bayu Intan; Oksto Ridho Sianturi; Yunia Witasari; Singgih Prasetyo Adi Wibowo; Mitsunori Iwataki (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
Dinoflagellate cysts have an important role for their bloom dynamics, which are commonly deposited along fine sediment grains and become the source of the next bloom. This study aimed to describe the cyst banks species composition, and their relationship with the sediment particles size and plankton composition in the coast of Pangkajene, South Sulawesi. Cysts observed in this study were extracted from seabed sediments collected from 9 sites. A potential cyst bank, with a cyst density of 240 cysts.g-1 sediment wet weight was found at PK-19, located in proximity to a large harbour complex. Although unusual, cyst density was significantly and positively correlated with the percentage of gravel. In contrast, the diversity of cysts seems to be affected by the percentage of fine sediments, such as silt and clay. None of the sediment composition was found strongly and significantly affecting both cyst density and diversity. A southward increase in cyst density was similar to the trend in the cell density of its planktonic form. Cysts of Protoperidinium spp., Scrippsiella spp., and Pheopolykrikos hartmannii were common and abundant in the sediment. Aside from Protoperidinium spp., most dinoflagellate species found in cyst form were absent from the water column. The occurrence of cysts of harmful dinoflagellates with records of devastating blooms in other coastal areas in Indonesia, such as Margalefidinium polykrikoides, Pyrodinium bahamense, and Gymnodinium catenatum, signifies a need to regularly monitor the area around Pangkajene coast to mitigate impacts of future blooms.